Pengembangan Video Tutorial Cara Penggunaan Face Tape untuk Rias Geriatri pada Mata Kuliah Tata Rias Wajah - Angelica Sugiono; Titin Supiani; Lilis Jubaedah (Journal on Education, 2025)
The result of the research carried out is a video tutorial that will be used as a learning medium in the Makeup Course. The video tutorials used have the aim of helping students to be able to properly understand the material being taught because these video tutorials can be watched and studied repeatedly without being hindered by limited time or space. The method used in the research carried out is the Research and Development method using the ADDIE model, ncludes Analysis, Design, Development, Implementation and Evaluation. This research and development has passed validation test by material and media experts, and practicality test by students. In the results of the validation test carried out by material experts, a score of 82% was obtained, which was in the "very worthy" category. Meanwhile, the validation test carried out by media experts obtained a score of 71.6% and was included in the "worthy" category. Then, a practicality test was carried out on 40 students of Jakarta State University, Cosmetology Education Study Program class of 2022, obtaining a score of 95.3% which was in the "very practical" category. Based on the results of a series of tests that have been carried out, the video tutorial "How to Use Face Tape for Geriatric Makeup" was declared suitable and practical to be used as a learning medium in the Makeup Course.